Risk factor analysis of endometriosis in women of reproductive age: a tertiary care level hospital study in Bangladesh - Panna, Benozir Haque; Siddiqua, Sehereen F.; Ara, Iffat; Sultana, Tahmina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Endometriosis is a disease in which tissue near the lining of the uterus grows outside the uterus. It can originate severe pain in the pelvis and make it harder to get pregnant. In several studies, several factors have been identified as the risk factors of endometriosis. But in Bangladesh, we have very limited research-based information regarding this issue. This study aimed to assess the risk factors of endometriosis in women of reproductive age. Methods: This case-control study was conducted in the department of obstetrics and gynecology, Anwer Khan modern medical college, Dhaka, Bangladesh from January 2019 to December 2019. As per the inclusion criteria, in total 24 women of reproductive age with endometriosis were enrolled in the case group (Group 1). On the other hand, 24 age-matched women without endometriosis were enrolled in the control group (Group 2). A purposive sampling technique was used in sample selection. All the demographic and clinical data were analyzed by using the SPSS version 23.0 program and disseminated by the MS office program. Results: In this study, assessing the risk factors of endometriosis among various reproductive histories of the participants revealed statistically significant correlations between the groups for the age of 30-40 years, late marriage, late childbearing, dysmenorrhea, and family history of endometriosis, with p values less than 0.05. However, when comparing genital tract obstruction, frequent and prolonged menstrual cycles, and nulliparity, we observed noticeable differences between the groups, but these were not statistically significant. Conclusions: Age of 30-40 years, late marriage, late childbearing, dysmenorrhea, and family history of endometriosis may be considered the potential risk factors for endometriosis in women of reproductive age.